Peran Keluarga di Era Pandemi Covid-19 terhadap Efikasi Diri Mahasiswa - Ahmad Thoriq Ihtisamul Haqqi; Febranti Putri Navion (Az-Zahra: Journal of Gender and Family Studies, 2022)
The spread of the COVID-19 virus has spread to many countries, including Indonesia. This has resulted in a very critical pandemic that disrupts the education process in Indonesia, making learning a learning system or home learning. The bold education system implemented during this pandemic made students feel difficult in the process of understanding the material being studied, this also made students unstable and could even be said to be low. This requires the role of the family towards students when studying from home. Therefore, the purpose of this is to explore and examine the role of research on students during the covid-19 pandemic.The method used in this research is descriptive qualitative research method. Researchers used in-depth interviews, observation, and documentation as credible data collection techniques. Meanwhile, in the process of data analysis, this research uses descriptive (non-statistical) data analysis. From this research process, it can be concluded that the family has many roles for students when doing courageous learning during the covid-19 pandemic. The various roles that families play for children who are undergoing online lectures are as follows: family as motivator, family as communicator, family as evaluator and family as facilitator.